Peningkatan Literasi Kesehatan Kader Posyandu dalam Mendukung Transformasi Layanan Kesehatan Primer di Kelurahan Lapulu - Purnamasari, Anisa; Nawawi, Nawawi; Lisnawati, Lisnawati; Nazaruddin, Nazaruddin; Ardiansyah, La Ode (Karya Kesehatan Journal of Community Engagement, 2025)
The transformation of primary health care services in Indonesia requires the active role of Posyandu cadres as the frontliners in delivering basic health services. However, in Lapulu Subdistrict, cadres still face limited knowledge and skills, particularly in effective communication as well as technical competencies such as weighing, anthropometric measurements, and recording in the Maternal and Child Health (MCH) handbook. This Lecturers’ Community Service Program (PKM) aimed to enhance health literacy among Posyandu cadres through participatory approaches of education, training, and mentoring. The program consisted of three stages: preparation (coordination, training module development, and evaluation tools), implementation (health literacy education, effective communication training, and technical skill practices through demonstrations, simulations, and peer teaching), and mentoring with evaluation. Knowledge improvement was assessed using pre-test and post-test, while skills were evaluated through observational checklists. The results showed a significant improvement in cadres’ knowledge, with the average score increasing from 58.7 (pre-test) to 83.5 (post-test). Technical skills competence also improved, from only 30% to 85% of cadres being able to perform anthropometric measurements and recording accurately. During mentoring, cadres demonstrated effective communication, correct measurements, and simple counseling to mothers. This PKM has proven effective in strengthening the capacity of Posyandu cadres through health literacy improvement. The program contributes to the implementation of primary health care transformation in coastal communities, positioning cadres not only as service providers but also as agents of change toward healthier, more empowered societies.